2013
DOI: 10.4314/ijbcs.v7i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food flavour enhancer (Monosodium Glutamate and Maggi Poulet) supplementation on glucose tolerance in <i>Sprague Dawley</i> rat

Abstract: This study was designed to evaluate the effects of purified monosodium glutamate and 'Maggi Poulet', on body weight gain, lipid profile, hepatic lipid peroxidation and glucose tolerance in rats. Thirty five young male Sprague Dawley rats were divided into five groups and fed by oral route as follow: group I (distilled water), group II (monosodium glutamate solution), group III ('Maggi Poulet'solution), group IV (monosodium glutamate solution. and high fat solution) and group V ('Maggi Poulet' solution and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…It leads to impaired regulation of hepatic glucose synthesis, declining beta-cell function, ultimately leading to beta-cell failure [22]. This finding agrees with Tchaou et al [23], which showed that overnight fasting glucose was not influenced by monosodium glutamate (MSG) and Maggi poulet solution injection. Another study found no effects of MSG administration on postprandial glycaemia and insulinemia [24], however, MSG-obese rats had impaired glucose tolerance and insulin resistance [25].…”
Section: N= Number Of Rats Ns= Not Significantsupporting
confidence: 83%
“…It leads to impaired regulation of hepatic glucose synthesis, declining beta-cell function, ultimately leading to beta-cell failure [22]. This finding agrees with Tchaou et al [23], which showed that overnight fasting glucose was not influenced by monosodium glutamate (MSG) and Maggi poulet solution injection. Another study found no effects of MSG administration on postprandial glycaemia and insulinemia [24], however, MSG-obese rats had impaired glucose tolerance and insulin resistance [25].…”
Section: N= Number Of Rats Ns= Not Significantsupporting
confidence: 83%
“…The liver damaging ability or hepatotoxic property of MSG found in instant noodle seasoning have been reported by many authors. A study conducted by Tchaou et al [33] showed that MSG consumption is hepatotoxic, and another work done by Diniz et al [34] found out that administration of MSG was associated with oxidative stress in hepatic tissues. The result was also in agreement with the work of Bopanna et al [7] who observed adverse effect on the liver of rats fed with food contaminated with monosodium.…”
Section: Discussionmentioning
confidence: 99%